STUDI KANDUNGAN CAPSAISIN CABAI RAWIT (Capsicum frutescens L.) AKIBAT PEMBERIAN MUTAGEN KIMIA EMS (ETHYL METHANE SULFONATE) - Arrufitasari, Putri Nur; Fikri, Galih El; Handini, Aline Sisi; Sutanto, Oentari Prilaningrum; Hidayatullah, Careca Sepdihan Rahmat (Agriculture Faculty of Flores University, 2025)
Chili pepper (Capsicum frutescens L.) is an important horticultural commodity in Indonesia with high economic value, primarily due to its capsaicin content, which provides its distinctive pungency and health benefits. This study aimed to evaluate the effect of Ethyl Methane Sulfonate (EMS) as a chemical mutagen agent on capsaicin content in the leaves and stems of three local chili pepper genotypes. The research was conducted using a two-factor Completely Randomized Design (CRD) with three replications, consisting of EMS concentrations (0.00%, 0.01%, 0.02%, and 0.04%) and three chili pepper genotypes. Mutation treatment was carried out by soaking seeds in EMS solution for six hours. Capsaicin content was analyzed using spectrophotometry at a wavelength of 280 nm. The results showed that EMS treatment had no significant effect on capsaicin content in either leaves or stems across all genotypes. However, there was a tendency for increased capsaicin content in certain treatment combinations, particularly at EMS concentrations of 0.01%. This suggests that EMS treatment at specific concentrations may induce physiological changes associated with capsaicin production.